2006
DOI: 10.1002/uog.3840
|View full text |Cite
|
Sign up to set email alerts
|

Complete extirpation of benign breast lesions with an ultrasound‐guided vacuum biopsy system

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 15 publications
1
22
0
9
Order By: Relevance
“…However, there has not been a study comparing these methods in terms of pain associated with the procedure, discomfort of the procedure, side effects and aesthetic results. Krainick-Strobel et al found that, in the case of the VAB biopsy, the average pain score associated with the procedure on a 10-point scale was 1.35 [9]. It coincides with the results of this study, which also showed no significant difference between the VAB biopsy and the BLES biopsy in terms of pain, discomfort or duration of the procedures.…”
Section: Discussionsupporting
confidence: 91%
“…However, there has not been a study comparing these methods in terms of pain associated with the procedure, discomfort of the procedure, side effects and aesthetic results. Krainick-Strobel et al found that, in the case of the VAB biopsy, the average pain score associated with the procedure on a 10-point scale was 1.35 [9]. It coincides with the results of this study, which also showed no significant difference between the VAB biopsy and the BLES biopsy in terms of pain, discomfort or duration of the procedures.…”
Section: Discussionsupporting
confidence: 91%
“…The microbiopsy approach is currently used in other oncology specialities, such as breast cancer [17], but not for skin cancer, where conventional biopsies range from 2 to 4 mm. This size range is key for enabling histopathological diagnosis.…”
Section: Future Oncologymentioning
confidence: 99%
“…direkt unter dem Befund zu platzieren, was die höhere Anzahl an entnommenen Biopsiezylindern, vor allem bei angestrebter KR, erklärt. Ko et al [8] [3] konnten zeigen, dass in vitro eine Größenzunahme des zu entfernenden Befundes mit einer verlängerten Untersuchungsdauer einhergeht, da mehr Gewebezylinder entnommen werden müssen, um die KR zu erreichen [10]. Bei Befunden > 20 mm gleicht die Zeit, die für die sonografisch geführte VB benötigt wird, in etwa der Eingriffsdauer einer ambulanten offenen Probenexzision.…”
Section: Diskussion !unclassified